Plan de negocio para la creación de una distribuidora mayorista de frutas y vegetales producidas sin químicos, cantón Quevedo, año 2014. - Tirado Mena, Jorge Fernando (2015)
This thesis is the development of a business plan for the wholesale of fruits and vegetables grown without chemicals, in Canton Quevedo, company called Good Earth Cia. Ltda. The idea was born on the basis of need by a niche market, where they are aware of the extreme exposure of fruit and vegetable fertilizers, pesticides, heavy metals like mercury and lead, that either the short or long term symptoms or diseases triggered degenerating health of consumers, including the much feared cancer. It aims to guide consumers who despite having a general idea of what the fruits and vegetables without chemicals, know the cost-benefit of food without chemicals versus traditional foods. By the proposition that the development of a wholesale distributor to reach the different districts of the city of Quevedo through distribution in stores, with a variety of quality product at an affordable price for the different socioeconomic levels. To achieve the above-described information was collected both primary and secondary levels by the author of the thesis, collected through a survey of the future customers of the company, data required for pricing and other economic-estimates financial....